Service Quality and Its İmpact on Customer Contentment and Brand Faith in Telecom Industry in Odisha-West Bengal - Radhika Badhan, Dr. Madhura Bedarkar (International Journal of Advanced Science and Technology, 2020)
Telecom providers play a significant role in the upliftment of the Indian economy and also helps in financial inclusion. India is one of the largest telecoms developing country with 1151.44 million users. The telecom sector has shown remarkable development in the last 5 years in the count of the userbase and high internet penetration. It has become very important for the telecom providers to fulfil its subscriber’s requirement in the competitive Industry. Customer is a key component for the success of any organization. However, gaps abound in the execution of customer service such that the businesses’ progress is frustrated. The study underlines how the service quality has an impact on user’s contentment in the Telecommunication Industry.The study has identified and analysed five parameters in service quality which is reliability, tangibility, responsiveness, empathy and assurance. The evolution of technologies in this sector has many pros and cons which will be discovered by conducting surveys of up to 300 subscribers of four Indian telecom service providers in Odisha-west Bengal region. The motive of this research is to spot factors affecting the quality of service providers in the Telecom Industry. Customers look for a seamless experience while using mobile networks. Customer contentment is the ultimate goal of every business and is a concept that is a comparison of service performance with the experience obtained from its conduct. Service quality and a user’s contentment are conceptually related. In the management of service quality, satisfaction is defined as emotional behaviour after purchase. Quality of service is an indicator in determining the success of a service.